Spatially Resolved Analysis of Stellar Populations in NGC 2992: Impact of Active Galactic Nucleus Feedback - Xu, Xiaoyu; Wang, Junfeng; Li, Zhiyuan; Chen, Yanmei (The Astrophysical journal, 2024)
In NGC 2992, a galaxy-scale ionized gas outflow driven by active galactic nuclei (AGNs) has long been recognized, yet its impact on the host galaxy has remained elusive. In this paper, we utilize data from the archival Very Large Telescope/MUSE to present a spatially resolved analysis of stellar populations in this galaxy. Two different stellar population templates are employed to fit the stellar continuum, allowing us to determine the light-weighted stellar age, metallicity, the fraction of the young stellar population (age <100 Myr, P Y ), and the average age and metallicity of P Y . Our results reveal the presence of a very young stellar population (≤40 Myr) within the dust lane and nearly along the galaxy’s major axis. The light-weighted stellar age and the fraction of P Y show negative trends along the major and minor axes. The average age and metallicity of P Y present positive trends with increasing distance, except along the northern direction of the major axis. Within the circumnuclear region (<1 kpc), the distribution of the young stellar population is spatially anticorrelated with the AGN outflow cone. The highest fraction of P Y is observed at the outskirts of the nuclear radio bubble in the northern region near the nucleus. Considering the coupling efficiency and timescales, we propose that the AGN outflow in this galaxy may exert both negative and positive feedback on its host. Additionally, the star formation and the AGN activities could be attributed to the interaction between NGC 2992 and NGC 2993.